The metamorphic sole of New Caledonia ophiolite: 40Ar/39Ar, U-Pb, and geochemical evidence for subduction inception at a spreading ridge - Cluzel, Dominique; Jourdan, Fred; Meffre, Sébastien; Maurizot, Pierre; Lesimple, Stéphane (American Geophysical Union, 2012)
Amphibolite lenses that locally crop out below the serpentinite sole at the base of the ophiolite of New Caledonia (termed Peridotite Nappe) recrystallized in the high-temperature amphibolite facies and thus sharply contrast with blueschists and eclogites of the Eocene metamorphic complex. Amphibolites mostly display the geochemical features of MORB with a slight Nb depletion and thus are similar to theyoungest (Late Paleocene–Eocene) BABB components of the allochthonous Poya Terrane. Thermochronological data from hornblende (40Ar/39Ar), zircon, and sphene (U-Pb) suggest that these mafic rocks recrystallized at ~56 Ma. Using various geothermobarometers provides a rough estimate of peak recrystallization conditions of ~0.5 GPa at ~80–95°C. The thermal gradient inferred from the metamorphic assemblage (~60°C km-1), geometrical relationships, and geochemical similarity suggest that these mafic rocks belong to the oceanic crust of the lower plate of the subduction/obduction system and recrystallized when they subducted below young and hot oceanic lithosphere. They were detached from the down-going plate and finally thrust onto unmetamorphosed Poya Terrane basalts. This and the occurrence of slab melts at ~53 Ma suggest that subduction inception occurred at or near to the spreading ridge of the South Loyalty Basin at ~56 Ma.